2022
DOI: 10.3233/jad-210607
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms Underlying Resistance to Dementia in Non-Demented Individuals with Alzheimer’s Disease Neuropathology

Abstract: Alzheimer’s disease (AD) is the most common form of dementia and typically characterized by the accumulation amyloid-β plaques and tau tangles. Intriguingly, there also exists a group of elderly which do not develop dementia during their life, despite the AD neuropathology, the so-called non-demented individuals with AD neuropathology (NDAN). In this review, we provide extensive background on AD pathology and normal aging and discuss potential mechanisms that enable these NDAN individuals to remain cognitively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 243 publications
(276 reference statements)
0
17
0
1
Order By: Relevance
“…Aβ is a centrally important compound in neurodegenerative diseases such as AD. When Aβ plaques and neuro brillary tangles are abnormally deposited, this causes synaptic damage that potentiates cognitive impairment, leading to memory loss, AD, and other neurodegenerative diseases (Kok et al, 2022). In AD, when Aβ oligomers bind to the postsynaptic membrane, this induces synaptotoxicity, so several treatment options to improve AD target Aβ to prevent or reduce Aβ-synaptic binding (Pinheiro & Faustino, 2019;Kok et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ is a centrally important compound in neurodegenerative diseases such as AD. When Aβ plaques and neuro brillary tangles are abnormally deposited, this causes synaptic damage that potentiates cognitive impairment, leading to memory loss, AD, and other neurodegenerative diseases (Kok et al, 2022). In AD, when Aβ oligomers bind to the postsynaptic membrane, this induces synaptotoxicity, so several treatment options to improve AD target Aβ to prevent or reduce Aβ-synaptic binding (Pinheiro & Faustino, 2019;Kok et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In non‐demented subjects with Aβ plaques, toxic Aβ oligomers were not localized in postsynaptic densities and therefore did not induce synaptic loss (Zolochevska et al, 2018 ). In a recent review investigating possible mechanisms preventing non‐demented individuals with Aβ plaques from cognitive impairment, it was found that Aβ oligomers do not bind to synapses and therefore do not induce synaptotoxicity and inflammation through glial activation (Kok et al, 2022 ).…”
Section: Characterization Of Soluble Brain‐derived Aβ ...mentioning
confidence: 99%
“…Disease-distinctive proteins exist in different states that aggregate between them: soluble monomers aggregate together to form dimers and oligomers, that can form soluble protofibrils. In turn, protofibrils aggregate to form insoluble fibrils, that eventually deposit in the form of plaques or tangles [ 8 ]. Soluble proteins are present in the CSF, and in equilibrium—either direct or inverse, depending on the molecule and the stage of the disease—with the concentration in the ISF ( Figure 1 ).…”
Section: The Bbb the Csf And The Neurodegenerative Diseasesmentioning
confidence: 99%
“…The process is dynamic and bidirectional, therefore complex aggregates can disaggregate into less complex aggregates. Modified from Kok et al, 2022 [ 8 ].…”
Section: Figurementioning
confidence: 99%